Synthesis of bifunctional fluorescent nanohybrids of carbon dots–copper nanoclusters via a facile method for Fe3+ and Tb3+ ratiometric detection. Issue 32 (22nd July 2021) - Lin, Shumin; Dong, Jiangxue; Zhang, Bangwen; Yuan, Zeming; Lu, Chunxiao; Han, Pei; Xu, Jia; Jia, Lina; Wang, Li
Abstract : A bifunctional fluorescent nanohybrids sensor is designed to realize the simultaneous detection of Fe 3+ and Tb 3+ in the same solution. Abstract : In this work, a dual-emission ratiometric fluorescent probe of carbon dots–copper nanoclusters (CDs–Cu NCs) nanohybrids with bifunctional features was successfully assembled through mechanical mixing. The CDs were synthesized using ascorbic acid as a carbon source, and Cu NCs were prepared using d -penicillamine as the stabilizer and reducing agent. The as-prepared CDs–Cu NCs displayed two emission peaks (blue at 424 nm and red at 624 nm) when excited at 360 nm, and showed great stability. Interestingly, trace amount of Fe 3+ could lead to the aggregation of Cu NCs, and induce a drastic static fluorescence quenching at 624 nm because of the electrostatic combination between them, while the fluorescence of the emission peak at 424 nm remained constant. Moreover, an attractive fluorescence enhancement phenomenon at 424 nm was observed when trace Tb 3+ was added to the above system, which may due to the combination of fluorescence resonance energy transfer (FRET) and photo-induced electron transfer (PET) mechanisms. Thus, CDs–Cu NCs were applied for the ratiometric detection of Fe 3+ and Tb 3+ in aqueous solution, and the detection limit (3σ/slope) was 45 nM and 62 nM with the linear range from 0.01 to 40 μM and 0.1 to 50 μM, respectively. Furthermore, the developed sensor was successfully applied for the detection of Fe 3+ and Tb 3+ in real-water samples.